Transforming growth factor-β signalling regulates protoscolex formation in the Echinococcus multilocularis metacestode - Kaethner, Marc; Epping, Kerstin; Bernthaler, Peter; Rudolf, Kilian; Thomann, Irena; Leitschuh, Nadine; Bergmann, Monika; Spiliotis, Markus; Koziol, Uriel; Brehm, Klaus (Frontiers in Cellular and Infection Microbiology, 2023)
The lethal zoonosis alveolar echinococcosis (AE) is caused by tumour-like, infiltrative growth of the metacestode larval stage of the tapeworm Echinococcus multilocularis. We previously showed that the metacestode is composed of posteriorized tissue and that the production of the subsequent larval stage, the protoscolex, depends on re-establishment of anterior identities within the metacestode germinative layer. It is, however, unclear so far how protoscolex differentiation in Echinococcus is regulated. We herein characterized the full complement of E. multilocularis TGFβ/BMP receptors, which is composed of one type II and three type I receptor serine/threonine kinases. Functional analyses showed that all Echinococcus TGFβ/BMP receptors are enzymatically active and respond to host derived TGFβ/BMP ligands for activating downstream Smad transcription factors. In situ hybridization experiments demonstrated that the Echinococcus TGFβ/BMP receptors are mainly expressed by nerve and muscle cells within the germinative layer and in developing brood capsules. Interestingly, the production of brood capsules, which later give rise to protoscoleces, was strongly suppressed in the presence of inhibitors directed against TGFβ/BMP receptors, whereas protoscolex differentiation was accelerated in response to host BMP2 and TGFβ. Apart from being responsive to host TGFβ/BMP ligands, protoscolex production also correlated with the expression of a parasite-derived TGFβ-like ligand, EmACT, which is expressed in early brood capsules and which is strongly expressed in anterior domains during protoscolex development. Taken together, these data indicate an important role of TGFβ/BMP signalling in Echinococcus anterior pole formation and protoscolex development. Since TGFβ is accumulating around metacestode lesions at later stages of the infection, the host immune response could thus serve as a signal by which the parasite senses the time point at which protoscoleces must be produced. Overall, our data shed new light on molecular mechanisms of host-parasite interaction during AE and are relevant for the development of novel treatment strategies.